Software quality assurance : - Godbole, Nina S. (Alpha Science International, 2005)
Software Quality Assurance (SQA) as a professional domain is becoming increasingly important. This book provides practical insight into the topic of Software Quality Assurance. It covers discussion on the importance of software quality assurance in the business of Information Technology, covers key practices like Reviews, Verification & Validation. It also discusses people issues and other barriers in successful implementatin of Quality Management Systems in organization. This work presents methodologies, concepts as well as practical scenarios while deploying Quality Assurance practices and integrates the underlying principle into a complete reference book on this topic.